Cardiolipin-Specific Phospholipase D Activity in Haemophilus parainfluenzae - Ono, Yoshie (1970)
A highly active phospholipase D that is specific for cardiolipin was detected in the gram-negative bacterium Haemophilus parainfluenzae. Previously reported phospholipase D preparations have come exclusively from higher plants. The bacterial enzyme hydrolyzed cardiolipin to phosphatidyl glycerol and phosphatidic acid. During the incubation, phosphatidic acid disappeared. Phosphatidyl ethanolamine, methylated phosphatidyl ethanolamines, phosphatidyl choline, and phosphatidyl glycerol were not hydrolyzed when cardiolipin was rapidly hydrolyzed.